Indigenous Plant-Based Alternatives for Treating Cattle Skin Ailments: A Case Study from the Mnisi Tribal Authority of Mpumalanga Province, South Africa - Maluleke, G; Masoko, P; Chitura, T (Asian Journal of Agriculture and Rural Development, 2022)
The study was carried out in the Mnisi Tribal Authority, Mpumalanga Province, South Africa, between August and October 2021. Ethno-veterinary data were collected using pre-structured questionnaires and field observations with cattle owners. The data were analyzed and summarized using descriptive statistics. Frequently mentioned plants belonged to the families Vitaceae (Cissus quandrangularis), Euphorbiaceae (Synadenium cupulare), Fabaceae (Dichrostachys cinerea), Solanaceae (Nicotiana batacum), Euphorbiacae (Jatropha zayheri), and Apocynaceae (Sarcostemma viminate). Antimicrobial susceptibility assays with ampicillin as positive control were carried out on extracts of Synadenium cupulare (aerial parts and leaves), Dichrostachys cinerea (seeds/ fruits), and Cissus quadrangularis (aerial parts and leaves). Aqueous extracts of S.cupulare (L) were the most effective against E. faecalis with the lowest MIC of 0.73 mg/ml, followed by aqueous extracts of Dichrostachys cinerea with an MIC of 1.36. Open wounds were the most common ailment (35%), followed by abscesses (23%) and abrasions (17%). Documenting Indigenous knowledge can be a basis for the development of sustainably used medicinal plants in the area and the validation of these plant preparations for veterinary use since the low cost of these preparations makes them useful for local communities.